Cultivating equality: delivering just and sustainable food systems in a changing climate - CARE; Rawe T; Food Tank; Deering, Karl; Echols W; Nierenberg D; Nink E; Ahern, C.; Small S (CARE, Food Tank, 2015)
T oday, the world faces a greater challenge perhaps than ever before: tackling hunger and malnutrition in the face of climate change and increasing natural resource scarcity. Civil society, governments, researchers, donors, and the private sector are simultaneously debating and collaborating to find solutions. But the dialogue is over-emphasizing food production. Improving yields is important, particularly in places where there is not enough food or where food producers live in poverty. But simply producing more is not enough to tackle hunger. Furthermore, acknowledging that lack of food is not the sole cause of hunger is important. Inequality shapes who has access to food and the resources to grow it and buy it. It governs who eats first and who eats worst. Inequality determines who can adapt more readily to a changing climate. Hunger and poverty are not an accident – they are the result of social and economic injustice and inequality at all levels, from household to global. The reality of inequality is no truer for anyone than it is for women – half the world’s population, with far less than their fair share of the world’s resources. If we are to achieve the new Sustainable Development Goal of ending hunger by 2030, we must address the underlying inequalities in food systems. In a changing climate, agriculture and food systems must be sustainable and productive – but our efforts cannot end there. They must be profitable for those for whom it is a livelihood; they must be equitable, to facilitate a level playing field in the market, to secure rights to resources for food producers, and to ensure access to nutritious food for all; they must be resilient to build the capacity of populations vulnerable to economic shocks, political instability, and increasing, climate-induced natural hazards to recover and still lift themselves out of poverty.